2022
DOI: 10.1111/jfpp.17175
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sodium alginate and sodium alginate/WPI as coating material on microcapsules of Jujube extract produced by spray dryer

Abstract: The aim of the research was to study the impact of various carrier types (sodium alginate and blend of sodium alginate with WPI) on the physicochemical, structural, and thermal characteristics of Jujube extract powder fabricated by spray drying. TPC and antioxidant activity, solubility, moisture, EE, powder yield, DSC, particle size, and morphology of powders were surveyed. The use of WPI resulted in powders with less moisture (10%), lower solubility (98.04%), and better powder yield (22.50%). WPI‐produced pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…The fast drying process and rapid water removal during spray drying can lead to flattening of particles and collapse of the spherical capsule walls [42] . Khoshdouni-Farahani et al [43] stated that jojoba extract capsules prepared by the spray drying method with isolated casein coating appeared as spherical particles with bulges in their microstructure. Ćujić-Nikolić et al [44] reported that grape pomace extract capsules prepared with maltodextrin had a more uniform spherical shape, smoother surfaces, and fewer cavities compared to capsules prepared with whey protein.…”
Section: Resultsmentioning
confidence: 99%
“…The fast drying process and rapid water removal during spray drying can lead to flattening of particles and collapse of the spherical capsule walls [42] . Khoshdouni-Farahani et al [43] stated that jojoba extract capsules prepared by the spray drying method with isolated casein coating appeared as spherical particles with bulges in their microstructure. Ćujić-Nikolić et al [44] reported that grape pomace extract capsules prepared with maltodextrin had a more uniform spherical shape, smoother surfaces, and fewer cavities compared to capsules prepared with whey protein.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the total phenol content, The Folin–Ciocalteu method was used 18 . For this purpose, first 1.6 mL distilled water was mixed with 20 μL of sample and 100 mL Folin solution was added (1:10, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the total phenol content, The Folin-Ciocalteu method was used. 18 For this purpose, first 1.6 mL distilled water was mixed with 20 μL of sample and 100 mL Folin solution was added (1:10, v/v). After 5 min, 300 μL sodium carbonate solution (7.5%) was added and its absorption (at 765 nm) was read after 2 h by a spectrophotometer (model Cary 300, Varian, Mulgrave, Victoria, Australia).…”
Section: Total Phenolic Compounds Of Al-ifpg Beadsmentioning
confidence: 99%
See 2 more Smart Citations